The Influence of Leadership Roles and Work Culture on the Performance of Police Members in Providing Public Services to the Community at Mendoyo Police - I Gusti Ngurah Made Dwi Arta Kumara; Muhammad Nur Afandi; Ida Ayu Putu Sri Widnyani (International Journal of Economics and Management Research, 2024)
The performance of police members of the Mendoyo Police is influenced by the existence of a good leadership role and a work culture that is in accordance with the environment in providing services to the community. Considering that there are still many cases or reports that have not been resolved, namely 14.20 % of cases, better performance from police members of the Mendoyo Police is needed. This study aims to determine and analyze the influence, both partially and simultaneously, between the role of leadership and work culture on the performance of police members in providing services to the community. This type of research uses a quantitative method that aims to find the causal influence of the independent variables, namely the role of leadership and work culture on the performance of police members in providing services to the community at the Mendoyo Police. The population in this study was 52 police members, and the method of determining the sample used the census method or saturated sample in which all populations were sampled, namely all members of the Mendoyo Police, totaling 52 people. The data analysis method used is multiple linear regression analysis with hypothesis testing using t-test and F-test. The results of the study indicate that the role of leadership and work culture have a partial and simultaneous effect on the performance of police members in providing services to the community at the Mendoyo Police. The variables of the role of leadership and work culture have an effect of 60.4 % on the performance of police members while the remaining 39.6% is influenced by other factors.